The bibliometric and visualization analysis of alcohol-induced osteonecrosis of the femoral head: research trends and future directions (1998–2024) - Kai Pang; Huiying Li; Haifeng Chen; Zhentao Man; Dandan Wang; Wei Li (Journal of Orthopaedic Surgery and Research)
Abstract Background Osteonecrosis of the femoral head (ONFH) is a progressive, debilitating orthopedic condition that primarily results from compromised vascular supply. Chronic alcohol intake is a well-established non-traumatic etiological factor in ONFH. Despite the increasing global research on ONFH, a bibliometric analysis using explicit literature searches in Web of Science reveals that no studies have specifically focused on alcohol-induced osteonecrosis of the femoral head (AONFH). This study aims to provide a comprehensive overview of the global research landscape of AONFH, identifying key research hotspots, emerging trends, and future directions using both qualitative and quantitative bibliometric methods. Methods The Web of Science Core Collection was systematically searched for publications from 1998 to 2024 related to AONFH and identified 353 relevant articles. RStudio and Bibliometrix 4.1.0 were used to analyze annual publication volume and cited papers. VOSviewer was employed to conduct bibliographic coupling analysis and CiteSpace was used to analyze countries, institutions, authors, journals, and keywords. Microsoft Excel 2019 was utilized to perform linear regression on annual publication volume. Results Clinical Orthopaedics and Related Research had the highest number of publications and citations. Chinese scholars published the most, while U.S.-based research received greater international recognition. Shanghai Jiao Tong University ranked first in institutional output. Sugano Nobuhiko and Fukushima Wakaba were identified as the most influential scholars. The main research hotspots—as measured by keyword centrality and frequency—were “risk factors” and “core decompression,” followed by “total hip arthroplasty,” “alcohol intake,” and “steroid-induced osteonecrosis.” Over time, the focus of AONFH research has shifted from broader themes such as “disease,” “smoking,” “occupational status,” and “idiopathic osteonecrosis” to more specialized areas including “gene expression,” “polymorphisms,” “steroid-induced osteonecrosis,” and “risk factors.” Conclusion AONFH research has progressed significantly, especially with its transition from basic science to precision medicine, including innovations such as genomics and stem cell therapy. Early diagnosis and intervention are critical to improving outcomes. Future research is expected to focus on refining the identification of risk factors, optimizing core decompression techniques, and incorporating precision medicine to enhance the quality of life and long-term prognosis of patients with AONFH.